Coil-Uncoiled Chain Transition of Polyethylene Oxide Solutions under Convergent Flow - Pogrebnyak, Andriy; Chudyk, Igor; Pogrebnyak, Volodymyr; Perkun, Iryna (Видавництво Львівської політехніки, 2019)
Досліджено перехід клубок-розгорнутий ланцюг при збіжній течії водних розчинів поліетиленоксиду. Експериментально підтверджено можливість такого переходу. Вивчено поля швидкостей і їх градієнтів, що виникають на вході короткого капіляра при збіжній течії. Встановлено, що система вода-поліетиленоксид при збіжній течії за певних режимів є саморегулюючою з негативним зворотним зв'язком. Показано, що зростаючі поздовжні градієнти швидкості призводять до деформації макромолекулярних клубків, що, в свою чергу, викликає перебудову структури потоку таким чином, щоб збільшити час впливу поздовжнього градієнта швидкості на макромолекули. Гідродинамічне поле, яке виникає в умовах збіжної течії, приводить до значного ступеня розгорнення молекул полімеру і до переходу клубок-розгорнутий ланцюг.

The coil-uncoiled chain transition under convergent flow of polyethylene oxide aqueous solutions has been studied. The possibility of this transition has been confirmed by the experiments. The fields of velocities and their gradients arising at the entrance of a small capillary during the convergent flow have been examined. It was found that water-polyethylene oxide system under convergent flow and certain flow regimes is self-regulating one with a negative feedback. The latter manifests itself in the following: accelerated longitudinal gradients of velocity lead to deformation of macromolecular coils, followed by a rearrangement of the flow in such a way as to increase the impact time of the longitudinal velocity gradient on macromolecules. The hydrodynamic field arising under the convergent flow provides a considerable degree of polymer uncoiling and coil-uncoil chain transition.
Перехід клубок-розгорнутий ланцюг при збіжній течії розчинів поліетиленоксиду
Keywords: макромолекула; розчин полімеру; клубок-розгорнутий ланцюг; збіжна течія; гідродинамічне поле; кінетичний фактор; показник заломлення; фазовий перехід; macromolecule; polymer solution; convergent flow; hydrodynamic field; kinetic factor; refraction index; phase transition